Penyuluhan Isolasi Mandiri Untuk Mengurangi Penyebaran Covid-19 Pada Pedagang Pasar Desa Pelas Kras Kediri - Nur Azizah Mufarikha; M. Faiz Amiruddin (LP3M IAIFA Kediri, 2021)
In 2020, humans were shaken by the corona virus which caused panic everywhere. Hundreds of thousands of people suffered from the virus and thousands more died. Corona virus is a virus that originates from animals and is transmitted through humans. Therefore, the government gives an appeal to the community in overcoming this outbreak, one of which is breaking the Covid-19 chain by means of self-isolation. But there are still many people who do not obey it. Health education activities are currently considered very important, especially in the market environment. Therefore, the program